The Mississippian emergence - Smith, Bruce D. (Bruce David), 1946- (University of Alabama Press, 2007)
This collection, addressing a topic of ongoing interest and debate in American archaeology, examines the evolution of ranked chiefdoms in the Midwestern and Southeastern United States during the period A.D. 700-1200. The volume brings together a broad range of professionals engaged in the fieldwork that has vitalized the theoretical debates on the development of Mississippi Valley cultures. The initial chapter provides a general discussion of various explanations for the rise of these distinctive ranked societies in the eastern United States (A.D. 750-1050) and sets the stage for the interdisc.